Accumulation characteristics on a cold, high-alpinef firn saddle from a snow-pit study on Colle Gnifetti, Monte Rosa, Swiss Alps - Haeberli, W.; Schotterer, U.; Wagenbach, D.; Haeberli-Schwitter, H.; Bortenschlager, S. (Journal of Glaciology, 1983)
In a snow pit, incorporating about 2.5 a of accumulation, on the 4450 m high Colle Gnifetti, Monte Rosa, various snow characteristics, isotopes (δ 18O, 3H), electrical conductivity, dust, trace elements, and pollen were investigated. The aim of this study was to develop a key for the stratigraphic interpretation of cores from cold, high-alpine firn areas. It appears that the strong influence of wind results in mixing and re-sedimentation processes in the surface layers. Nevertheless, by interpreting several parameters in a combined way, it is possible to classify a large number of the layers according to their season and sometimes to their place of origin. Apart from the melt layers, which only appear in early summer to summer layers, other prominent features are the (Saharan) dust falls, characterized by dust and conductivity peaks. Diverses caractéristiques de la neige, isotopes (δ 18O, 3H), conductivité électrique, poussières, trace d’éléments et pollen ont été étudiés dans une tranchée englobant environ deux ans et demi d’accumulation neigeuse afin de déterminer une «clef» pour l’interprétation stratigraphique des carottages dans les régions de névés froids en haute-montagne sur le Colle Gnifetti (4450 m s.m., Mont Rose). On observe que la forte influence du vent mène à des phénomènes de mélange et de résédimentation des couches superficielles. Toutefois, sur la base de l’information tirée de la combinaison des différents paramètres observés, il est possible de dater une grande part des couches de neige et parfois d’en déterminer l’origine. En plus des horizons de glace, qui n’apparaissent que dans les couches estivales, des indices marquants sont les poussières sahariennes, caractérisées par la pointe de teneur en poussière et de conductivité. An einem rund 2.5 Jahresschichten umfassenden Schneeschacht auf dem 4450 m hohen Colle Gnifetti, Monte Rosa, wurden diverse Schneecharakteristiken, Isotopen (δ 18O, 3H), elektrische Leitfähigkeit, Staub, Spurenelemente und Pollen untersucht. Ziel dieser ...